2013
DOI: 10.1039/c3cp50463h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectroscopy and dynamics: a polyad-based perspective

Abstract: The efficiency and insight of global, polyad-based modeling in overtone spectroscopy and dynamics is demonstrated. Both vibration and vibration-rotation polyads are considered. The spectroscopic implications of polyad Hamiltonians derive from their ability to account for the detailed line positions and intensities of spectral features and their unique predictive power. The dynamical implications of polyad Hamiltonians include classical bifurcations that lead to the birth of new vibrational modes and intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 392 publications
(462 reference statements)
0
48
0
1
Order By: Relevance
“…[33] In Sandorfy's modelH ,a ll hydrogen and carbon (or silicon) orbitals are considered, but it has been rarely if ever used to gain simple intuitive insight, because it is still very complex. Sandorfy model Cf or alkanes (or oligosilanes), whichc onsiders only two orbitals on each carbon (or silicon) within ac hain, is more suitable.H owever,b oth Sandorfy modelsa re oversimplified for our purposes,s incet hey give the same result for all conformations of am olecule.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…[33] In Sandorfy's modelH ,a ll hydrogen and carbon (or silicon) orbitals are considered, but it has been rarely if ever used to gain simple intuitive insight, because it is still very complex. Sandorfy model Cf or alkanes (or oligosilanes), whichc onsiders only two orbitals on each carbon (or silicon) within ac hain, is more suitable.H owever,b oth Sandorfy modelsa re oversimplified for our purposes,s incet hey give the same result for all conformations of am olecule.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…1 Evidence for IVR in the frequency domain comes from splittings, shifts, and broadening of lines, that can lead to very rich discretely resolved spectra on one end, or poorly resolved, heavily broadened spectra on the other. 15 The transition from well resolved to heavily broadened spectra was elegantly captured by Boyarkin et al in their study focusing on highly excited vibrational states of CH 3 OH, where they found an exponential increase in the degree of broadening due to IVR in going from the 2 nd to 8 th OH stretching overtone. 16 The effect of the helium nanodroplet environment on IVR processes is expected to be modest, at most, and this is based on a previous study on the first overtone spectroscopy of chromophores in helium nanodroplets that have differing degrees of IVR, which dictates the linewidths in the gas phase.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to supporting reaction dynamics [65], including isomerization processes [66][67][68][69][70], overtone excitation is recognised as driving some of the atmospheric chemistry [71][72][73] and as controlling bond selected chemistry [74,75]. The investigation of overtones generated the local mode theory [76][77][78], the polyad concept [79,80], and, as already suggested, stimulated the development of detection capabilities [81][82][83][84].…”
Section: Introductionmentioning
confidence: 98%